Colonization resistance and establishment success along gradients of functional and phylogenetic diversity in experimental plant communities. (19th August 2019) - Galland, Thomas; Adeux, Guillaume; Dvořáková, Hana; E‐Vojtkó, Anna; Orbán, Ildikó; Lussu, Michele; Puy, Javier; Blažek, Petr; Lanta, Vojtěch; Lepš, Jan; de Bello, Francesco; Pérez Carmona, Carlos; et al.
Abstract: Functional and phylogenetic diversity (FD and PD respectively) of the resident community are expected to exert a key role in community resistance to colonization by surrounding species, and their establishment success. However, few studies have explored this topic experimentally or evaluated the interactive effects of these diversity measures. We implemented a diversity experiment to disentangle the role of FD and PD by sowing mixtures of 6 species, drawn from a pool of 19 species naturally coexisting in central European mesic meadows. The mixtures were designed to cover four independent combinations of high and low FD and PD. Species covers were estimated in spring and late summer over two growing seasons. We then assessed the establishment success of colonizers as a function of their mean traits and phylogenetic distance to the resident (i.e. sown) communities, as well as the resistance of the resident communities to natural colonizers as a function of their functional and phylogenetic structure. Results generally indicated a temporal shift regarding which trait values made a colonizer successful, from an acquisitive strategy in early stages to a more conservative trait syndrome in later stages. FD decreased community resistance to natural colonization. However, PD tempered this effect: with high PD, FD was not significant, suggesting complementary information between these two components of biodiversity. On average, colonizing species were more functionally distant from the resident species in sown communities with high functional diversity, i.e. those that were more colonized. Synthesis. Our results confirm an interplay between FD and PD during community assembly processes, namely resistance to colonizers, suggesting that these two descriptors of biodiversity only partially overlap in their contribution to the overall ecological structure of a community. The hypothesis that higher FD increases resistance through a more complete use of resources was challenged. Results rather suggested that greater FD could provide an unsaturated functional trait space allowing functionally unique species to occupy it. Abstract : Interplay between FD and PD in plant community resistance to colonization: We present the first field experiment with orthogonal combinations of high and low FD and PD. Results suggest that FD and PD only partially overlap in their contribution to the overall ecological structure of a community. Greater FD provides an unsaturated functional trait space allowing functionally unique species to occupy it.